Coupled effects of earthquake and rainfall on landslide susceptibility in non-tropical coastal areas: assessing governing mechanisms and innovative slope protection strategy - Prabhakar Khadka; Oladoyin Kolawole; Andrew C. Amenuvor; Mawuko L. Y. Ankah (Discover Civil Engineering)
Abstract Despite extensive research on landslides globally, there is a notable knowledge gap on mechanisms influenced by combined rainfall and earthquake events to induce landslides in non-tropical coastal areas, and how to mitigate such failures. This study assessed the factors governing landslide susceptibility in the non-tropical coastal regions under the combined influence of rainfall and earthquake, and further proposes a novel slope protection work that can potentially mitigate such hazard. Adopting datasets from two distinct coastal regions in the United States, this study employed both the Limit Equilibrium Method (LEM) and the Finite Element Method (FEM). Hazard analysis was conducted using Factor of Safety (FoS) from LEM and Strength Reduction Factor (SRF) from FEM on the identified slopes to gain insights into combined rainfall- and earthquake-induced landslides. The results indicate that LEM exhibits limitations in reliability of slope stability analysis with complex failure mechanisms, and is primarily suitable for simple slopes without the influence of non-anthropogenic activities. Contrarily, FEM demonstrated relatively superior applicability for stability analysis of the slopes with complex failure mechanisms and under the influence of environmental stressors in coastal regions. FEM-based assessment of slopes under the dry state and the combined state (earthquake and rainfall) conditions revealed high susceptibility to failure in non-tropical coastal areas under the combined state conditions. Coupled earthquake and rainfall influence on soil mass slopes in non-tropical coastal areas induced shear strain propagation and matric suction reduction along shallower depths, leading to decreased slope stability. Further, we proposed a novel slope protection work that demonstrated higher efficiency in reducing shear strain and increasing SRF (+ 16%), presenting a potentially viable slope protection strategy for non-tropical coastal areas.